Sosialisasi Profesi Akuntansi untuk Meningkatkan Minat dan Motivasi Pelajar SMK Muhammadiyah 9 Jakarta dalam Menghadapi Persaingan Dunia Kerja - Nani Jumanti; Sarah Ari Sofura; Aulia Rahmi; Cici Rosmala; Satria Berbudi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
e lack of public knowledge of the accounting profession. Even though as long as the business world and offices still exist, the ability and skills in accounting are still needed. The accountant profession is a problem not only because of technological developments but also because of the lack of socialization and promotion related to the output of accounting majors, so that students experience confusion in determining their interests and expected profession. In the digital era, there are concerns that the accounting profession may no longer be needed in the business world. This opinion is based on the perception that more affordable, fast, and accurate accounting software can replace the role of accountants, causing challenges for this profession. Therefore, the socialization of the accounting profession can be used as an opportunity from the threats that will be faced in the future. Socialization is given in the form of lectures, questions and answers and discussions from discussions that are carried out one day considering the busy learning of XII grade vocational students. The results of this socialization were that the participants were very enthusiastic about the material presented because the speakers delivered the material with light language adapted to today's gen Z children, participants could listen to the material well and followed by a question and answer session. The final evaluation was a positive response and good enthusiasm from the students of SMK Muhammadiyah 9 Jakarta along with the teachers of the socialization.